2021
DOI: 10.21203/rs.3.rs-654509/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of Downstream Effectors of Retinoic Acid Specifying the Zebrafish Pancreas by Integrative Genomics.

Abstract: Retinoic acid (RA) is a key signal for the specification of the pancreas. Still, the gene regulatory cascade triggered by RA in the endoderm remains poorly characterized. In this study, we investigated this regulatory network in zebrafish by combining RNA-seq, RAR ChIP-seq and ATAC-seq assays. By analysing the effect of RA and of the RA receptor (RAR) antagonist BMS439 on the transcriptome and on the chromatin accessibility of endodermal cells, we identified a large set of genes and regulatory regions regulate… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 40 publications
(63 reference statements)
0
3
1
Order By: Relevance
“…In contrast, previous studies using higher concentrations of atRA (1 µM) showed the opposite effect, i.e. body axis truncation (33), suggesting that the effect of RA signaling is highly dose-dependent. Indeed, lower concentrations of atRA require more exposure time to produce morphological effects (57).…”
Section: Discussioncontrasting
confidence: 74%
See 3 more Smart Citations
“…In contrast, previous studies using higher concentrations of atRA (1 µM) showed the opposite effect, i.e. body axis truncation (33), suggesting that the effect of RA signaling is highly dose-dependent. Indeed, lower concentrations of atRA require more exposure time to produce morphological effects (57).…”
Section: Discussioncontrasting
confidence: 74%
“…In this sense, a recent report used dissected embryonic trunks from Aldh1a2 knockout mice and identified CREs switching epigenomic state in the absence of RA near well-known RA target genes in the trunk (32). More recently, another study used endodermal cells from zebrafish embryos treated with RA or the inverse agonist BMS493, and found alterations in chromatin accessibility associated with genes involved in pancreatic development (33). Here, we have taken advantage of a zebrafish-specific antibody to profile the dynamic chromatin binding of the RA receptor RARaa by ChIP-seq through early development, covering from gastrulation to the phylotypic stage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations